Evaluation of hydrogel formulated with seaweed extract (Ulva lactuca) for incised wound healing in white rats (Rattus norvegicus) - Stephanie Taniwan; Refi Ikhtiari; Stephanie Taniwan; Fiska Maya Wardhani (Jurnal Teknologi Laboratorium)
Skin, as the largest organ in the human and animal body, serves as the main protection against various external factors such as sharp objects, extreme temperatures, chemicals, or physical trauma. This study aims to evaluate the effectiveness of seaweed (Ulva lactuca) extract-based hydrogel in accelerating incision wound healing in Rattus norvegicus rats. This experimental study used a post-test only controlled group design with six treatment groups: Ulva lactuca hydrogel 5%, 10%, 15%, positive control (Bioplasenton), negative control (wound without treatment), and rat group without treatment. Data were analyzed using ANOVA test. The results showed that Ulva lactuca hydrogel 5% gave the best results in accelerating wound healing. The wound diameter in the 5% group decreased significantly, from 15.3 cm on day 0 to 10.9 cm on day 3, 4.7 cm on day 6, and 2.36 cm on day 14. Histopathology results showed increased epithelialization, decreased inflammation, and increased collagen deposition in the 5% group compared with the control group. Quantitatively, the 5% hydrogel group achieved wound healing up to 30% faster than the positive control and 50% faster than the negative control. The 5% Ulva lactuca hydrogel proved to be most effective in accelerating wound healing by modulating inflammation and promoting tissue regeneration. This concentration provides an optimal balance between efficacy and safety, making it a potential alternative for wound therapy.